2020
DOI: 10.29252/jhsme.7.2.2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Spiritual-Religious Interventions on Anxiety, Depression, and Adjustment to Parental Divorce in Female High School Students

Abstract: Children who experience parental divorce undergo crisis, shock, and disruption of their sense of security and psychological well-being (5). Besides, it causes behavioral problems, and reduces their adaptability (7); however, the impact of divorce may vary with the age of the children (6). According to the results of a study conducted by Seijo et al., children of divorce were more likely to have symptoms of depression, anxiety, aggression, paranoid thoughts, social isolation, social exclusion, and I

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
(21 reference statements)
1
2
0
Order By: Relevance
“…In this regard, the effectiveness of the religious coping intervention of REBT could be attributed to the use of religious imagery and disputation techniques to demonstrate how depressive or anxiety conditions could be managed or eliminated in one life. This finding aligns with the finding of Kahrizeh et al, [ 27 ] which revealed that spiritual-religious intervention substantially reduced anxiety and depression. Furthermore, this finding of this study supports the previous study showing that religiosity has a positive impact on improving T2DM management.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In this regard, the effectiveness of the religious coping intervention of REBT could be attributed to the use of religious imagery and disputation techniques to demonstrate how depressive or anxiety conditions could be managed or eliminated in one life. This finding aligns with the finding of Kahrizeh et al, [ 27 ] which revealed that spiritual-religious intervention substantially reduced anxiety and depression. Furthermore, this finding of this study supports the previous study showing that religiosity has a positive impact on improving T2DM management.…”
Section: Discussionsupporting
confidence: 92%
“…On the effectiveness of the religious intervention, Kahrizel et al, [ 27 ] used a quasi-experimental study to investigate the effect of the spiritual-religious intervention on anxiety, depression and adjustment to parental divorce among female schoolchildren. The results revealed that spiritual-religious intervention significantly affected participants’ anxiety, depression, and adjustment to parental divorce.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation